PENINGKATAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL ENGKLEK PADA ANAK USIA 5-6 TAHUN: Penelitian Tindakan Kelas (PTK) - Irma Siti Maharani; heri yusuf muslihin; qonita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aimed to improve the gross motor skills of Group A students through the traditional game of engklek. The study used a Classroom Action Research (CAR) approach based on the spiral model by Kemmis & McTaggart, which involved two cycles, each consisting of planning, implementation, observation, and reflection. The subjects consisted of 13 students, and data was collected through observation and interviews. The results showed a significant improvement in students' gross motor skills. The average pre-action scores were all in the BB category (100%). After Cycle I, the scores increased to the MB category (46%) and BSH (53%). In Cycle II, the scores increased again to the BSH category (23%) and BSB (76%). Interviews revealed that learning through the traditional game of engklek provided a pleasant experience for students. With teacher guidance, the process of playing engklek became more engaging and enjoyable. Based on these findings, this study concludes that the use of the traditional game of engklek is effective in improving children's gross motor skills. Keywords: Gross motor skills, engklek, traditional game